2020
DOI: 10.32479/ijeep.8118
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption, Information and Communication Technology and Economic Growth in an African Context

Abstract: The study had two main objectives. Firstly, to investigate the impact of ICT on economic growth. Secondly, to explore whether energy consumption and human capital development are channels through which ICT influences economic growth in Africa. Whilst literature is unanimous when it comes to the positive impact of ICT on economic growth, not much has been investigated on the impact of the complementarity between (1) ICT and energy consumption and (2) ICT and human capital development on economic growth, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…In addition, stationary time series were used to calculate the unknown parameters of models (2) and (3). The analysis results confirmed that widespread tests for checking the time series stationarity were Dicky-Fuller and Phillips-Perron tests (Akimova et al 2017;Raheem et al 2020;Chimbo 2020;Arshad et al 2020). Thus, the main stage of estimating the impact of innovation and information technology on greenhouse gas emission were:…”
Section: Methodssupporting
confidence: 70%
See 2 more Smart Citations
“…In addition, stationary time series were used to calculate the unknown parameters of models (2) and (3). The analysis results confirmed that widespread tests for checking the time series stationarity were Dicky-Fuller and Phillips-Perron tests (Akimova et al 2017;Raheem et al 2020;Chimbo 2020;Arshad et al 2020). Thus, the main stage of estimating the impact of innovation and information technology on greenhouse gas emission were:…”
Section: Methodssupporting
confidence: 70%
“…On the contrary, the scientists Chimbo (2020) and Raheem et al (2020) proved that ICT has a negative impact on GDP and CO 2 emissions. Further, Chimbo (2020) confirmed that, for African countries, spreading of ICT led to an increase of energy consumption. Chimbo (2020) and Raheem et al (2020) estimated ICT by the following variables: telephone landlines, mobile phone penetration and internet penetration.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The empirical findings imply an affirmative and vigorous effect of using ICT infrastructure on economic augmentation, although the amount of the benefit varies depending on the type of technology studied. Similarly (Chimbo, 2020), ICT increased economic growth through its energy efficiency effect in Africa by using the GMM model from 2001 to 2015. Since ICT and human development have remained important topics in recent years, Gupta et al (2019) evaluated how evolution in ICT could stimulate human capital advancement for the South Asian region over the period of 2000 to 2016 by using the panel fixed effects model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Elfaki et al (2020 state that there is a reciprocal relationship between electricity consumption, international trade openness, and economy in Sudan. Chimbo, (2020) expresses that there is a link between energy consumption, human capital development through communication and information technologies and a nation's economic growth.…”
Section: Introductionmentioning
confidence: 99%